2014
DOI: 10.1016/j.matbio.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

A rapid increase in macrophage-derived versican and hyaluronan in infectious lung disease

Abstract: The goals of this study were to characterize the changes to chondroitin sulfate proteoglycans and hyaluronan in lungs in the acute response to gram-negative bacterial infection, and to identify cellular components responsible for these changes. Mice were treated with intratracheal (IT) live Escherichia coli, E. coli lipopolysaccharide (LPS), or PBS. Both E. coli and LPS caused rapid selective increases in mRNA expression of versican and hyaluronan synthase (Has) isoforms 1 and 2 associated with increased immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 78 publications
2
89
0
Order By: Relevance
“…24,25 In addition, studies have confirmed that increases in versican expression influence cell adhesion, proliferation, migration, and survival as well as regulation of key inflammatory response. [26][27][28] Versican accumulation in the subepithelial layer in airways of atopic asthmatics has been described previously and correlates with the degree of AHR to methacholine challenge. 16 In addition, increased versican accumulation is associated with both small and large airway remodeling seen in autopsy specimens following fatal asthma exacerbations.…”
Section: Discussionmentioning
confidence: 70%
“…24,25 In addition, studies have confirmed that increases in versican expression influence cell adhesion, proliferation, migration, and survival as well as regulation of key inflammatory response. [26][27][28] Versican accumulation in the subepithelial layer in airways of atopic asthmatics has been described previously and correlates with the degree of AHR to methacholine challenge. 16 In addition, increased versican accumulation is associated with both small and large airway remodeling seen in autopsy specimens following fatal asthma exacerbations.…”
Section: Discussionmentioning
confidence: 70%
“…Versican expression, typically present at low levels in most adult tissues, is increased in the lung during experimentally induced inflammation (Gill et al 2010;Chang et al 2014). In human lungs, versican accumulation is increased in many pathological conditions (Bensadoun et al 1996(Bensadoun et al , 1997Lowry et al 2008;Merrilees et al 2008;Gill et al 2010;Chang et al 2014;Wight et al 2014a). Versican expression in the CNS is also increased following injury and altered in diseases such as multiple sclerosis (Fawcett and Asher 1999;Schmalfeldt et al 2000;Sobel and Ahmed 2001;Asher et al 2002;Gu et al 2007).…”
Section: Research-article2015mentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described (Fu et al 2011;Chang et al 2014). Briefly, all embryos were pretreated with Chondroitinase ABC for 1 hr and HIER1 (Citrate) for 10 min before combining with rabbit antimouse β-GAG antibody (#1033, lot #2006928; Millipore, Billerica, MA) for 1 hr at 2 µg/ml to detect for versican accumulation.…”
Section: Versican and Dpeaae Quantitative Immunohistochemistrymentioning
confidence: 99%
“…Versican expression, which is high in lungs during embryonic development (7-9) but low in adult lungs, is reactivated in numerous lung diseases, including pulmonary fibrosis, chronic obstructive pulmonary disease, acute respiratory distress syndrome, and asthma (10 -18). Our published work has shown that versican and molecules that associate with versican, such as HA, are the principal ECM components that accumulate in inflamed lungs at early times following exposure to pathogens, such as LPS (19). The accumulation of a versican-enriched ECM coincides with invasion and retention of leukocytes within different compartments of the lung during these early inflammatory responses.…”
mentioning
confidence: 94%